The RNAi as a tool to control tropical pathogens - Hernández-Soto, Alejandro (2021)
Introduction. Sustainable farming requires new tools for the control of pathogens, since there is a constant evolution to overcome the current biological and chemical strategies. The information provided by the transcriptomics allows creating new possibilities to tackle the pathogens. It is possible to interrupt the genetic expression of a pathogen and disable it using RNA interference (RNAi). Objective. To perform an analysis of an emerging technology useful for pest control, based on RNA interference. Development. Sustainable farming is measured based through social, economic, and environmental indicators. A key indicator of agriculture is the decrease in inputs for the control of pathogens and the increase in their specificity. Pest control mechanisms based on RNA interference meet both parameters. RNAi is known to have at least two functions, first for gene expression regulation, and secondly as a defense mechanism against pathogens. Consequently, RNAi can be used to protect crops from pathogens by developing genetically modified plants, or by the external application form of an aerosol. The RNAi aerosol is a tool that relies on inactivating the pathogen genes and can complement other agronomic tools available for this purpose. It is possible to design RNAi against tropical pests based on published transcriptomes, although it is necessary to overcome limitations regarding design, degradation, and stability. Conclusion. Interference RNA methods have the potential to be useful tools to control tropical pathogens as an alternative to achieve sustainable farming.